Design of Low Noise Amplifier for WLAN using pHEMT - Thirunavukkarasu, G.; Murugesan, G. (International Journal of Engineering and Technology, 2020)
The low power consumption devices are frequently focused in design and manufacturing wireless communication system. This paper gives a systematic design of a low noise amplifier for WLAN application aimed to obtain minimum noise figure. The simulation result shows that the noise figure is in the appreciable level (1.67 dB). The maximum gain is greater than 10 dB. These are the predominant requirements of an LNA. Also it posses good stability and the LNA design uses pHEMT for its appreciable noise performance.Â Â